Correlation between the level of orthodontic treatment need and dental anxiety among undergraduate dental students: Study observasional - Gabriella, Rut Sahatna; Laviana, Avi; Suryanti, Netty (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRAKIntroduction: The aesthetic component of the Index of Orthodontic Treatment Need (IOTN-AC) assesses the need for orthodontic treatment as well as its psychosocial impact. One common psychosocial impact is dental anxiety, which can hinder individuals from undergoing orthodontic treatment. This study aimed to analyze the level of orthodontic treatment need using IOTN-AC and dental anxiety, as well as to analyze the correlation between both variables among dental students. Methods: This correlational analytic study with an observational approach employed a purposive sampling technique involving dental students of Universitas Padjadjaran. Data were collected online through a Google Form containing a dental anxiety questionnaire and IOTN-AC assessment. The subjects consisted of 46 active undergraduate dental students from the 2021 and 2022 batches who had never received fixed or removable orthodontic treatment. Data were analyzed using the Spearman rank correlation test. Results: A total of 60.9% of respondents did not require orthodontic treatment, 28.3% had a mild need, and 10.8% had a moderate need. Among those with no treatment need, 6.5% reported no anxiety, 26.1% low anxiety, 24% moderate anxiety, and 4.3% high anxiety. Among those with mild to moderate treatment need, 2.2% reported no anxiety, 15.2% low, 17.4% moderate, and 4.3% high anxiety. Spearman’s test showed a negative correlation between treatment need and dental anxiety (p=0.032; r=-0.506). Conclusions: The higher the level of orthodontic treatment need, the lower the level of dental anxiety among dental studentsKEY WORDS: Index of orthodontic treatment need, dental anxiety, malocclusion, undergraduate studentsKorelasi antara tingkat kebutuhan perawatan ortodonti dengan dental anxiety mahasiswa program studi sarjana kedokteran gigi: Studi observasionalABSTRACTPendahuluan: Komponen estetika Index of Orthodontic Treatment Need (IOTN-AC) menilai kebutuhan perawatan ortodonti serta dampak psikososialnya. Dampak psikososial yang umum terjadi adalah dental anxiety yang dapat menghambat individu menjalani perawatan ortodonti. Penelitian ini bertujuan untuk menganalisis tingkat kebutuhan perawatan ortodonti menggunakan IOTN-AC dan dental anxiety serta korelasi antara keduanya pada mahasiswa kedokteran gigi. Metode: Penelitian analitik korelasional dengan pendekatan observasional dan menggunakan teknik purposive sampling pada mahasiswa Kedokteran Gigi Universitas Padjadjaran, Pengumpulan data secara daring melalui google form yang berisi kuesioner dental anxiety dan penilaian IOTN-AC. Subjek penelitian adalah 46 mahasiswa aktif Kedokteran Gigi Universitas Padjadjaran angkatan 2021, 2022 dan belum pernah mendapatkan perawatan ortodonti cekat maupun lepasan. Analisis data menggunakan uji korelasi rank spearman; Hasil: 60,9% responden tidak membutuhkan perawatan ortodonti, 28,3 kebutuhan ringan, dan 10,8% kebutuhan sedang. Responden yang tidak membutuhkan perawatan menunjukan 6,5% tidak cemas, 26,1% kecemasan rendah, 24% kecemasan sedang, 4,3% kecemasan tinggi. Kebutuhan perawatan ringan dan sedang menunjukkan 2,2% tidak cemas, 15,2% kecemasan rendah, 17,4% kecemasan sedang dan 4,3% kecemasan tinggi. Uji spearman menunjukan korelasi negatif antara tingkat kebutuhan perawatan ringan dan sedang dengan tingkat dental anxiety (p-value=0,032; r= -0,506). Simpulan: Semakin tinggi tingkat kebutuhan perawatan ortodonti, maka tingkat dental anxiety cenderung semakin rendah pada mahasiswa sarjana kedokteran gigi.KATA KUNCI: Indeks kebutuhan perawatan ortodonti, dental anxiety, maloklusi, mahasiswa